Virginia Woolf’s Orlando, Coleridge, and Jane Ellen Harrison - Whitworth, M (Oxford University Press, 2017)
In Virginia Woolf’s Orlando (1928) one of the markers of cultural difference between the protagonist and the gypsies she meets in Turkey is linguistic: they have no word for ‘beautiful’, and when Orlando wishes to remark the beauty of a sunset, she has to point and to say, in their language, ‘good to eat.’ In a recent edition of the novel, I suggested that Woolf’s source for the idea may have been Samuel Taylor Coleridge. However, my annotation does not tell the entire story. The classicist and anthropologist Jane Ellen Harrison notes in her Themis: A Study of the Social Origins of Greek Religion (1912), that in at least two languages, Hebrew and what she calls ‘Mexican’, the word for ‘good’ meant ‘good to eat’.